Supramolecular rulers enabling selective detection of pure short ssDNA via chiral self-assembly. Issue 2 (2nd November 2015) - Kocsis, Istvan; Rotaru, Alexandru; Legrand, Yves-Marie; Grosu, Ion; Barboiu, Mihail
Abstract : TPA propellers appear to be compatible with the general requirements for amplified chiral supramolecular rulers used to determine the number of base pairs of short ssDNAs. Abstract : Multivalent self-assembly of trifunctional aromatic propellers and ssDNA results in the formation of chiral supramolecular assemblies that can be used for the detection of small fragments of ssDNA with different lengths and compositions.